2019
DOI: 10.1016/j.ejogrb.2018.11.005
|View full text |Cite|
|
Sign up to set email alerts
|

Smoking cessation support and obstetric outcomes in an Irish maternity hospital

Abstract: Background: Most European countries have seen a decrease in the prevalence of adolescent smoking. This decrease has, however, been patterned by gender. Girls' smoking rates have now overtaken boys' in many European countries. The two genders may not, however, share the same smoking beliefs and this could explain differences between the genders in smoking prevalence. We describe gender differences in smoking beliefs and investigate variations between countries, along with their gender context. Methods: In 2016,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Smokers are defined as people currently smoking at least one cigarette per day. Previous studies have indicated that smokers have a mean birthweight at term approximately 300 g lower than that of non‐smokers . We estimated that by using a standard deviation of ± 500 g, a statistical power of 80%, and a 5% level of significance (two‐sided), 44 women would be needed to detect a true difference in difference in birthweight means between smokers and non‐smokers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smokers are defined as people currently smoking at least one cigarette per day. Previous studies have indicated that smokers have a mean birthweight at term approximately 300 g lower than that of non‐smokers . We estimated that by using a standard deviation of ± 500 g, a statistical power of 80%, and a 5% level of significance (two‐sided), 44 women would be needed to detect a true difference in difference in birthweight means between smokers and non‐smokers.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have indicated that smokers have a mean birthweight at term approximately 300 g lower than that of non-smokers. 22,23 We estimated that by using a standard deviation of AE 500 g, a statistical power of 80%, and a 5% level of significance (two-sided), 44 women would be needed to detect a true difference in difference in birthweight means between smokers and nonsmokers. As EC users were an unknown entity without published birthweight estimates, we compared EC users with a larger group of smokers (99) and non-smokers (108) to ensure detection of a minimum difference of 300 g, assuming 80% power.…”
Section: Methodsmentioning
confidence: 99%
“…The risk of LBW was 2.19 times higher among study participants who had tobacco smoke exposure during pregnancy. Tobacco exposure as a risk factor for low birth weight has been reported in studies from developed countries [87,89,90]. Potential mechanisms underlying this association include an increased concentration of cotinine and nicotine in the amniotic fluid of the newborn leading to nicotine-induced placental vasoconstriction, a reduced blood oxygen uptake, increases in carboxyhemoglobin, or an increased occurrence of placental vascular disease, all of which affect fetal growth [91].…”
Section: Plos Onementioning
confidence: 99%
“…A higher proportion of continued cigarette smoking is encountered in lower socioeconomic groups. Our previous research shows that the needs of pregnant smokers are largely unmet and under-resourced [19]. Smokers are a different population to non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…An anticipated challenge for this study is retention of participants in the clinical trial, as our previous work has shown a relatively high rate of non-attendance amongst smokers for antenatal clinic appointments [19]. Additionally, should a smoker develop certain complications (most commonly, diagnosis of gestational diabetes requiring metformin or insulin treatment), she will require transfer out to another specialist antenatal clinic, leading to drop out.…”
Section: Discussionmentioning
confidence: 99%